TLR2 and the NLRP3 inflammasome mediate IL-1β production in Prevotella nigrescens-infected dendritic cells - Jang, Hye-Mi (Int J Med Sci, 2021)
Prevotella nigrescens is an oral pathogen that is frequently observed in the subgingival plaque of periodontitis patients. Interleukin-1β (IL-1β) is known to be involved in the immunopathology of periodontal diseases and has been implicated in the destruction of bone. In this study, we investigated the mechanism of IL-1β production by P. nigrescens in murine bone marrow-derived dendritic cells (BMDCs). Our results showed that a host receptor, Toll-like receptor 2 (TLR2), but not TLR4 is required for pro-IL-1β induction and nucleotide-binding oligomerization domain like receptor pyrin domain containing 3 (NLRP3) priming in BMDCs in response to P. nigrescens and activation of the NLRP3 inflammasome is necessary for processing of pro-IL-1β into mature IL-1β. In addition, an inhibitor assay revealed that production of reactive oxygen species, P2X(7)R activity, and release of cathepsin B are involved in IL-1β production in BMDCs in response to P. nigrescens.